Peran Kepemimpinan Perempuan dalam Manajemen Konflik Pembinaan Karakter Anak Asuh di Panti Asuhan Cahaya Mitra Arofah Surabaya - Izzatul Millah; Dina Zahrotun; Ahmad Khairul Hakim (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study is motivated by the growing role of female leadership in faith-based social institutions, particularly in managing conflicts and shaping the moral character of foster children amid complex social dynamics. The research aims to analyze how female leaders at Yayasan Cahaya Mitra Arofah Surabaya integrate spiritual and managerial values in addressing conflicts and fostering sustainable character development among foster children. Using a qualitative case study approach, data were obtained through in-depth interviews, participatory observation, and documentation involving the female leader, staff, and foster children, and analyzed using the Miles, Huberman, and Saldaña (2014) model comprising data reduction, display, and conclusion drawing. The findings indicate that female leadership in this institution is transformational–spiritual in nature, emphasizing moral exemplarity, empathy, and maternal approaches in conflict resolution and character formation. Internal conflicts are resolved through musyawarah (deliberation) and islah (reconciliation) grounded in Qur’anic and Prophetic values, while character education is carried out through habitual worship, discipline, and accountability. The study concludes that female leadership rooted in Islamic spirituality fosters organizational harmony, strengthens child discipline, and offers a humanistic and adaptive leadership model for other religious social institutions.